Excessive Social Inequality as a Serious Challenge to the Demographic Security of Mod-ern Russia with Considering the Supply Chain Strategy Effects - Dmitrii Aleksandrovich Koloskov; Ludmila Aleksandrovna Kormishkina; Evgenii Danilovich Kormishkin; EkaRevazievna Ermakova (International Journal of Supply Chain Management, 2019)
The article substantiates the idea that increasing social inequality and persistent large-scale poverty in post-Soviet Russia should be considered as one of the main reasons for the low birth rate in the country and a serious challenge to ensuring its demographic security. The authors propose a concept of demographic security and outline its primary indicators and their threshold values—the methodological basis for diagnosing and forecasting demographic processes from the perspective of Russia’s national and economic security. The authors analyzed the influence of excessive social inequality on the demographics in the country for the period from 1990 to 2018. The authors used a step-by-step analysis algorithm and built a multiple regression equation that reflects the impact of various socio-economic factors, including excessive inequality and deformation of people’s social behavior, on life expectancy. The equation has a high explanatory power (the adjusted coefficient of determination isṜ2= 0.914).Thus, it can be used as the methodological basis when proposing measures for maintaining and increasing life potential of society that is an optimal solution for ensuring demographic security in present conditions. The study presents recommendations on the development of an active national socio-economic policy aimed at overcoming excessive social inequality in Russia and ensuring its demographic security.